Controlled release of resveratrol and xanthohumol via coaxial electrospinning fibers. Issue 4 (3rd March 2020) - Zhang, Xue; Han, Libin; Sun, Qihao; Xia, Wenlong; Zhou, Qifeng; Zhang, ZhuanZhuan; Song, Xiaofeng
Abstract: Synergistic delivery of two drugs is a desirable choice to overcome drug resistance. Resveratrol (RES) and xanthohumol (XAN) which are both new drugs originated from plants exhibit great potential in the treatment of cancer, but there are few studies on combining them in a delivery system. In this work, a new core/shell fiber mesh containing RES and XAN was designed out via coaxial electrospinning, and the effect of drug content on the medicated fibers was discovered. RES/polyethylene oxide (PEO) could be well combined with XAN/Poly(lactide-glycolide) (PLGA) to make core/shell fibers, but fibrous morphology worsened with increasing drug content of the core or shell to some extent. The core/shell was amorphous nature, and changing drug content had little influence on the wetability of the core/shell fibers. The release accelerated with drug content increasing in the fibers, and RES and XAN showed gradient release, which the release rate of RES was slower than XAN. These two drugs could sustain release for 350 h. When the blend ratios of RES/PEO and XAN/PLGA were 50/50 and 10/90 in the fibers, the fiber mesh showed the best mechanical properties, of which the tensile strength and elongation at break were 2.85 ± 0.10 MPa and 55.23 ± 2.53%, respectively. The medicated fibers presented good characteristics of inhibiting breast cancer cell activity.